Human-Robot Collaboration in Industrial Engineering: Enhancing Productivity and Safety - Charles Onyeka Nwamekwe; Igbokwe Nkemakonam Chidiebube; Ono Chukwuma Godfrey; Nwabunwanne Emeka Celestine; Aguh, Patrick Sunday (Journal of Industrial Engineering & Management Research, 2025)
Human-Robot Collaboration (HRC) is revolutionizing industrial engineering by integrating collaborative robots (cobots) into shared workspaces to enhance productivity, safety, and operational efficiency. This research explores the paradigm shift from traditional automation to human-centric Industry 5.0 principles, focusing on cobots' role in addressing ergonomic challenges, optimizing workflows, and ensuring safe human-robot interaction. It emphasizes the adaptability of cobots to various applications, from manufacturing to logistics, showcasing their potential to transform industrial processes. Key topics include the evolution of cobots, their industrial use cases, and the ergonomic benefits they provide by reducing workplace injuries and enhancing worker well-being. Case studies highlight successful cobot implementations in automotive, assembly, and logistics industries, underscoring their role in fostering productivity and creating safer, more ergonomic work environments. By addressing both technical and ergonomic dimensions, this research provides a comprehensive overview of HRC's current state and future directions, offering insights into how cobots can harmoniously integrate human ingenuity with robotic efficiency for sustainable industrial progress.